Effects of open-skill exercise on executive functions in children and adolescents: a systematic review and meta-analysis - Hu, Shunding; Shi, Peng; Zhang, Ziyun; Feng, Xiaosu; Zhang, Kai; Jin, Teng (Frontiers in Human Neuroscience, 2025)
BackgroundThe research on the intervention of open-skill exercise on the executive functions of children and adolescents still requires quantitative synthesis, and there is inconsistency in the effects of intervention by strategic and interceptive skills, which are sub-divided from open-skill exercise. Therefore, this study systematically explores the aforementioned issues and examines the potential moderating factors in the effects of open-skill exercise intervention on executive functions.MethodsComputer searches of the CNKI, WOS, PubMed, ScienceDirect and SPORTDiscus databases were conducted. Two researchers independently screened the articles and extracted data, and used the bias risk assessment tool recommended by the Cochrane Collaboration Network and the Methodological Index for Non- Randomized Studies (MINORS) scale to assess included randomized controlled trials (RCTs) and quasi-experimental designs (QEDs). Statistical analyses were performed using Stata 16.0 software.ResultsA total of 16 articles and 17 studies were included, comprising 11 RCTs and 6 QEDs. The participants were 1,298 children and adolescents aged 5 to 16. Open skill exercises have significant intervention effects (p < 0.01) on inhibitory control (SMD = −0.627, 95%CI = −0.890 to −0.363), working memory (SMD = −0.517, 95%CI = −0.768 to −0.266), and cognitive flexibility (SMD = −0.652, 95%CI = −1.085 to −0.219). The effects of strategic skill exercises are higher than those of interceptive skills, particularly in the dimension of inhibitory control (SMD = −0.707, 95%CI = −0.819 to −0.594, p < 0.05). In addition, moderate-intensity and higher-frequency exercises overall have a more positive effect on promoting executive functions (p < 0.05); interventions of 6 to 10 weeks are more effective for working memory (p < 0.05), while 30-min sessions are the most effective for working memory (p < 0.05), and sessions lasting 75 to 120 min are the most effective for cognitive flexibility (p < 0.05). Open-skill exercise has a more positive impact on inhibitory control in the 5–9 age group and on working memory in the 10–16 age group (p < 0.05); open-skill exercise, especially, has a more positive intervention effect on inhibitory control in the Eastern group (p < 0.05). Both Egger linear regression analyses and literature sensitivity analyses suggested that the Meta-analysis results were stable and reliable.ConclusionOpen-skill exercise has a positive intervention effect on executive functioning in children and adolescents, and strategic skill exercise interventions are more effective. In addition, the quantitative elements of exercise (intensity, frequency, and duration per session) and demographic factors (age and ethnicity) play a potential moderating role in this context. Based on this, it is recommended that children and adolescents choose more strategic open-skill exercises according to their actual situation and select appropriate quantitative exercise factors to maximize the enhancement of their executive functions.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, CRD42025636714.